PENGARUH STRUKTUR CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN LINGKUNGAN (Studi Empiris pada Perusahaan Non-Keuangan yang terdaftar di Bursa Efek Indonesia Periode 2011-2013) - Natasya Elisabeth Nainggolan; Abdul Rohman (Diponegoro Journal of Accounting, 2015)
This study aimed to obtain empirical evidence about the influence of corporate governance structure to the extent of environmental disclosure. Corporate governance used 3 (three) proxy, that is gender diversity in board director, proportion of board independence, and institutional ownership. To measure the extent of environmental disclosure used carbon emission disclosure checklist. The population of this study was all non-financial companies listed in Indonesia Stock Exchange (ISX) in 2011-2013. Samplingis done by using purposive sampling method. There were 34 companies in 2011, 29 companies in 2012 and 2013 which fulfilled criterion as the research sample. This study used multiple linear regression analysis for testing the influence of independent variables on dependent variable. The results of this study showed that board independence and institutional ownership significantly influence to the extent of environmental disclosure. Meanwhile gender diversity had no significantly influence to to the extent of envirenmental disclosure.